What can be learned from variability in offshore wind projects. (January 2022) - Lerche, Jon; Lindhard, Søren; Enevoldsen, Peter; Velaayudan, Arumugam; Teizer, Jochen; Neve, Hasse H.; Wandahl, Søren
Abstract: The focus of this study was to learn from the operational variabilities in offshore wind projects by investigating the overall delays in offshore wind projects related to arrival time (flow) or job time (process-time) variability. This research was motivated by the general understanding that flow variability is dominant within the offshore wind domain. The case study presented is based on 183, 197 historical data-points from six different cases, the selection of cases was based on overall controllable project features. The findings reveal that from a variability perspective onshore performs better than offshore. The distribution also reveals that the process-time variability is dominant for both the onshore and offshore assembly location. This indicates that the offshore wind project variabilities are controllable and oppose the general understanding within the body of knowledge, however, further research would be required to understand the probable causations. The analysis and its results can be used for later predictions of project schedule outcomes or as explicit external knowledge for comparison. The results of this research project are relevant to both academics and practitioners, not only in offshore wind projects, but also onshore wind and other operations handling remote assembly locations. Highlights: Variability within onshore assembly location performs better than offshore assembly location. Project features as water depth, shore distance, and foundations are insignificant to variability. Results oppose understanding within offshore wind that flow variability dominates productivity. Process-time variability indicates that productivity can be planned for and controlled.